1985
DOI: 10.1097/00000658-198511000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Changes in T Lymphocyte Subsets Following Injury

Abstract: The increased susceptibility of severely injured patients to infection and death from sepsis has been attributed to abnormalities in cell-mediated immunity. The authors therefore assessed the relative number of peripheral blood T helper cells and T suppressor/cytotoxic cells and total T lymphocytes identified by the monoclonal antibodies (McA) OKT4, OKT8, and OKT3, respectively, in 25 patients with burns from 5 to 85% total body surface area (TBSA) (mean: 40%) and 21 patients with nonthermal injuries (mean Inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The importance of this finding is underscored by the importance of the helper/inducer (CD4+/CDw29+) T-cell subset in activating monocytes and other cells responsible for the destruction of Staphylococcus aureus and other common pathogens seen following severe head injury (McLean et al, 1975;O'Mahony et al, 1985;Abo et al, 1986;Morgan et al, 1984;Damle et al, 1986;Nencioni et al, 1983;Klimpel et al, 1988). Specifically, the helper/inducer (CD4+/CDw29 + ) T-cell subset is believed to be the human analog of the murine TH, cell, which has been characterized in animal models as the T cell producing IL-2, INF-G, and other cytokines responsible for the upregulation of cellular immunity.…”
Section: Depression Of Helper/inducer (Cd4+/cdw29+) T-cell Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of this finding is underscored by the importance of the helper/inducer (CD4+/CDw29+) T-cell subset in activating monocytes and other cells responsible for the destruction of Staphylococcus aureus and other common pathogens seen following severe head injury (McLean et al, 1975;O'Mahony et al, 1985;Abo et al, 1986;Morgan et al, 1984;Damle et al, 1986;Nencioni et al, 1983;Klimpel et al, 1988). Specifically, the helper/inducer (CD4+/CDw29 + ) T-cell subset is believed to be the human analog of the murine TH, cell, which has been characterized in animal models as the T cell producing IL-2, INF-G, and other cytokines responsible for the upregulation of cellular immunity.…”
Section: Depression Of Helper/inducer (Cd4+/cdw29+) T-cell Expressionmentioning
confidence: 99%
“…Although cellular immunity has classically been cited in immune surveilance against intracellular bacterial, viral, and fungal infections, several studies have demonstrated the importance of cellular immunity in defending against pyogenic bacterial and nonintracellular bacterial infections (McLean et al, 1975;O'Mahony et al, 1985;Abo et al, 1986;Morgan et al, 1984;Damleetal., 1986;Nencioni et al, 1983;Klimpel et al, 1988). Recent studies of alveolar macrophages in humans have shown that intact cellular immune function involving T-cell activity is required for clearing of Staphylococcus aureus following ingestion by polymorphonuclear cells and alveolar macrophages (McLean et al, 1975;O'Mahony et al, 1985;Abo et al, 1986). This pathogen accounts for the majority of infections seen in the acute phase following severe head injury, underscoring the clinical relevance of alterations in cellular immunity that occur after head injury (Helling et al, 1988;Quattrocchi et al, 1990Quattrocchi et al, , 1991aMilleret al, 1991;Hoyt et al, 1990).…”
Section: Relationship Of Infectious Complications To Immune Dysfunctionmentioning
confidence: 99%
“…T lymphocyte subpopulations, studied as a marker of trauma-induced stress in burn and postoperative models, have been found to correlate with degree of insult [11,27]. Interleukin-6 (Il-6) and C-reactive protein (CRP) levels, studied extensively as markers of operative stress in open surgery, have been used to compare the stress response in laparoscopic and open surgery with somewhat conflicting results [ [9,10,13,26,[28][29][30]32].…”
mentioning
confidence: 99%
“…We sought to determine the relationship between body composition changes and in vivo hepatic levels of pretranslational message for cachectin (messenger RNA) in a burn and infection rodent model. Adult Wistar rats were grouped as follows: (1) (1) scald burn only (n = 10), (2) scald burn and infection (n = 10), (3) freely fed controls (n = 14) anesthetized and submerged in thermoneutral water, (4) (Fig 1).…”
mentioning
confidence: 99%